HUBUNGAN PENGETAHUAN DAN SIKAP SISWA TERHADAP KEBERSIHAN LINGKUNGAN SEKOLAH DI SMA NEGERI I KECAMATAN TIGO NAGARI KABUPATEN PASAMAN. - Darlianis, Darlianis; Ahmad, Ridwan; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
Â This research aim to get information, analysing and studying data about knowledge relation and student attitude to hygiene of environment go to school in SMA Country of I District Of Tigo Nagari Sub-Province of Pasaman. Type Research the used is descriptive of correlational. Research population is students at SMA Country of I District Of Tigo Nagari Sub-Province of Pasaman which consist of 14 class, with amount of student 418 people. Research Sampel in this research [is] taken with technique of propousional sampling random equal to 15% from amount of population so that thereby the amount of sampel that is 63. Pursuant to analysis of regresi linear modestly is, double (multiple) hence can be taken by the following conclusion: (1) There are relation knowledge of student to hygiene of environment go to school SMA Country of I District Of Tigo Nagari Sub-Province of Pasaman, where variable knowledge of studentÂ have contribution to equal to 11,8% with hygiene of environment go to school SMA Country of I District Of Tigo Nagari Sub-Province of Pasaman, (2) There are student attitude relation to hygiene of environment go to school SMA Country of I District Of Tigo Nagari Sub-Province of Pasaman, bigly contribution 16,4% and (3) There are relation which [is] significant and positive among student attitude and knowledge by together with hygiene of lingkugan go to school SMA Country of I District Of Tigo Nagari Sub-Province of Pasaman, bigly contribution 27,0%.